2013
DOI: 10.1056/nejmoa1304572
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept in B7-1–Positive Proteinuric Kidney Disease

Abstract: Summary Abatacept (cytotoxic T-lymphocyte–associated antigen 4–immunoglobulin fusion protein [CTLA-4–Ig]) is a costimulatory inhibitor that targets B7-1 (CD80). The present report describes five patients who had focal segmental glomerulosclerosis (FSGS) (four with recurrent FSGS after transplantation and one with primary FSGS) and proteinuria with B7-1 immunostaining of podocytes in kidney-biopsy specimens. Abatacept induced partial or complete remissions of proteinuria in these patients, suggesting that B7-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
346
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(360 citation statements)
references
References 15 publications
9
346
2
3
Order By: Relevance
“…Sirolimus may accelerate progression of FSGS and should be avoided (93). Ongoing and recently completed phase 3 trials have shown some efficacy with sparsentan, an irbesartan-like molecule that also antagonizes endothelin receptor, and abatacept, a CD80 antagonist (121).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Sirolimus may accelerate progression of FSGS and should be avoided (93). Ongoing and recently completed phase 3 trials have shown some efficacy with sparsentan, an irbesartan-like molecule that also antagonizes endothelin receptor, and abatacept, a CD80 antagonist (121).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…There have been isolated case reports documenting resolution of recurrent FSGS in patients who received abatacept in doses that have been utilized for the treatment of systemic lupus erythematosus [81]. However, this observation has not been replicated by other investigators who failed to achieve permanent remission in patients with recurrent FSGS [82].…”
Section: Treatmentmentioning
confidence: 99%
“…Serum and urinary CTLA-4 levels tend to be low in MCD patients in relapse, and the urinary CTLA-4 level returns to higher levels during remission [95]. Yu et al described the use of abatacept in inducing remission in five patients with FSGS based on positive staining for CD80 in glomerular podocytes, reporting a clinically significant reduction in proteinuria in all patients [96]. However, the validity of these findings were questioned by other researchers [97,98].…”
Section: Abataceptmentioning
confidence: 99%